Improvement of Human Resources Capacity And Management of Payo Agro Tourism as an Efforts to Improve Local Economy - Adek Kurnia Fiza; Ernawati Ernawati; Arif Ardian; Susanti Retnaningtyas (Universitas Negeri Padang, 2020)
Tourism has become the driving force for the economy in the community, various regions have applied the pattern, and managed to have a positive impact. This condition is the background of research on the success of the community service program from the Padang State University (UNP) team in Tanah Garam Village. The study was conducted in June to November 2019, the method used was a qualitative approach. Primary data were obtained from interviews with the Head of Tourism and Culture of the City of Solok, community leaders in Tanah Garam, Pokdarwis Payo, and community members in the Payo area (Tanah Garam). Interviews were conducted in accordance with guidelines related to the success of the UNP community service program in increasing the capacity of human resources (HR) and the ability to manage Payo agrotourism, thus providing economic impact for the community. The results showed that the service program succeeded in improving the economy of the community after the ability to manage tourism was increased.